Processos de educação Akwẽ e os direitos indígenas a uma educação diferenciada: práticas educativas tradicionais e suas relações com a prática escolar - Xerente, Ercivaldo Damsõkekwa Calixto (2016)
This paper deals with the educational reality of the Akwẽ / Xerente people, with the objective of understanding the relations between their own oral model of education, and the educational models and practices based on writing. To do so, I describe the system and processes of formation and socialization of Akwẽ and Warã youngs, an educational institution, managed by the elderlies, who are responsible for this formation. I also observed the daily practices of the Kakumhu / Riozinho village and the Wakõmẽkwa school, places chosen to perform the ethnographic research. The main interlocutors of the survey were the village elders and sages, as well as the teachers of the mentioned school. The results of the research reveal, on the one hand, a contradiction between the two models of addressed education. On the other hand, they also reveal a search for dialogue between them and between the specific knowledges of each one. This search for dialogue is perceived mainly in the discourses and practices of teachers, who believes that traditional knowledges should be valued and incorporated into the school curriculum. The elders, on the other hand, demonstrate distrust of the school and teachers and point out many restrictions on the socialization of knowledge for all in school. This is because the Akwẽ society is subdivided into clans and each of them considers a sacred and particular patrimony the knowledge they have been keeping, from generation to generation. It is necessary that the community take ownership of your school and, at the same time, it earns the trust of your community. I also see the need for consensus, in which are agreed upon the types of knowledges that can be shared in the school.